Mathematics Communication Skill Viewed from Self-Confidence in Auditory Intellectually Repetition (AIR) Learning Model with RME Approach - Yunitiara Rizqi, Hesti; Waluya, S. B.; Wiyanto, Wiyanto (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics communication skill viewed from self-confidence of the students in AIR learning model with RME approach. This mixed method research used sequential explanatory. The population was taken from VII graders of 1 Pamotan, consisting of seven classes. The subjects were grouped based on self-confidence consisting of high, moderate, and low categories by using purposive sampling. Each subject was interviewed about mathematics communication skill. The findings showed that mathematics communication skill description viewed from self-confidence of the students was varied. It was shown from 11 students with high self-confidence obtained mathematics communication skill into 8 high and 3 moderate category students. From 14 students with moderate self- confidence, there were 4 students with high category, 8 students with moderate category, and 2 students with low category. From seven students with low self-confidence, there were 2 students with moderate and 5 students with low categories.